DEVELOPING STUDENTS' COMPETENCE IN LEARNING THROUGH LISTENING BASED ON THE COGNITIVE APPROACH - Kholboyeva Shokhsanam Anvarjon qizi (Web of Journals Publishing, 2025)
This article examines the issue of developing students' competence in learning through listening based on the cognitive approach. It discusses how audiobooks can be used to improve students’ reading and research skills, how they facilitate the reception, analysis, and retention of information through listening. Furthermore, it outlines the advantages of using audiobooks during lessons and in independent learning, as well as methodological approaches and results based on experimental data.
Keywords: Cognitive approach, audiobook, learning through listening, competence, media tools, independent learning, critical thinking.